Effectiveness of Antenatal Class Education in Improving Early Detection of Pregnancy Danger Signs - Riska Sabriana; Jusni; Hartati; Muh. Faizal Mardi Saleh (Jurnal Ilmiah Kesehatan Sandi Husada, 2025)
Introduction: Maternal mortality remains a significant public health concern in Indonesia, with inadequate early detection of pregnancy danger signs contributing significantly to preventable complications. Maternal classes are one of the key educational strategies aimed at improving pregnant women’s knowledge and awareness related to pregnancy risks. This study aimed to analyze the effectiveness of maternal class education in improving early detection abilities regarding pregnancy danger signs among pregnant women in UPT Puskesmas Ulaweng, Bone Regency. Methods: his study applied a pre–pre-experimental design using a one-group pretest–posttest approach. A total of 30 pregnant women were selected through quota sampling. Data were collected using an observation sheet and a questionnaire assessing early detection abilities. Statistical analysis was performed using the Wilcoxon signed-rank test to determine differences before and after the educational intervention. Results: Pretest findings indicated that 70% of participants had low early detection abilities, while only 13% demonstrated good ability. Following the maternal class intervention, 84% of participants achieved good ability, with only 3% remaining in the low category. The Wilcoxon test showed a significant difference between pretest and posttest scores (p = 0.003), indicating a substantial improvement in early detection skills after participating in the maternal class. Conclusion: The findings of this study indicate that maternal class education plays a crucial role in improving pregnant women’s ability to identify early danger signs during pregnancy. A significant increase in post-intervention scores, supported by the Wilcoxon test result (p = 0.003), confirms that the educational sessions effectively enhance maternal knowledge and vigilance. Strengthening early detection skills is essential for preventing complications and ensuring the safety of both mother and fetus. Based on these results, it is recommended that maternal classes be implemented consistently and systematically at the primary healthcare level. The involvement of husbands and family members is also encouraged to optimize support and facilitate timely decision-making when danger signs arise.